(3GdJcedI dcJGH GdUdIs - (3CHh YHO Gddg eMeO Hf CHi HcQ GdbVGYi Hf GdCdHGQ GdHdfSis; (3Nda Hf YHO Gdedc Hf eSYhO Hf nHrTocnhGd GdNRQLqj GdCfUGQj GdCfOdSj, CHh GdbGSe,J (B578 (3g` s
(3ChdgG (B:s
(3hGVWQH hJHGjf MGdjgG HChd TgQ GdeMQe eaJJM SfI EMOi hKdGKjf hSJeGFI s
(3BNQgG (B:s
(3Qhi Yfg GHfg CHh HcQ QHjT Hf eMeO , hbQCJ HNWg Cf CHGg YUQ jhe GdKdGKGA hChd GdKGfi eMeO Hf eMeO , hbQCJ HNWg Cf CHGg YUQ jhe GdKdGKGA hChd GdKGfi eMeO Hf eMeO Hf Ydi GdYci s
(3ef fSNI KGfjI HgG JeRjbs
(3JHUQI GdYfhGf (B:s
(3JPjjds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B311 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B105s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B341 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B581 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B122 s
Keywords: (3GdJGQjNs